Students’ mental health problems before, during, and after COVID-19 lockdown in Italy - Meda, Nicola; Pardini, Susanna; Slongo, Irene; Bodini, Luca; Zordan, Mauro Agostino; Rigobello, Paolo; Visioli, Francesco; Novara, Caterina (Journal of psychiatric research, 2021)
The lockdown due to the coronavirus pandemic may have exacerbated mental health problems. To what degree mental health may be affected by social isolation is still poorly known. We collected prospective data on students’ mental health in two instances: (i) in October and December 2019, and (ii) 6 months later, in April 2020 amidst the COVID-19 lockdown in Italy and in mid-May/June 2020, after the lifting of lockdown. A total of 358 Italian students aged 18–30 completed socio-demographic questionnaires and the Beck Depression Inventory – 2 (BDI-2), the Beck Anxiety Inventory (BAI), the Obsessive-Compulsive Inventory – Revised (OCI-R), the Eating Habits Questionnaire (EHQ), and the Eating Disorder Inventory-3 (EDI-3). We applied multiple regression models to evince any changes in the aforementioned questionnaire scores during and after lockdown with respect to the scores before lockdown. Students reported on average worse depressive symptoms during lockdown than 6 months before isolation (median increase in the BDI-2 score +2; IQR = −3, 6; β = 0.09 ± 0.03, p = 0.005), with students without any established diagnosis of psychopathology being affected the most. The regression models predict that 86.2% (IQR = 67.9, 91.4%) of students would not experience a clinically significant worsening of symptoms, while approximately 6% of our target population could develop more severe depressive symptoms. This study supports the view that depressive symptomatology may be aggravated during lockdown, but also highlights that after the lifting of lockdown any changes quickly vanished, as the BDI-2 scores were not different from the ones reported before lockdown. •Students report worse depressive symptoms during lockdown than 6 months before isolation.•86.2% of students would not experience a clinically significant worsening of symptoms.•After the lifting of lockdown any changes quickly vanish.•Anxiety and obsessive symptoms are not aggravated by lockdown.